Computational fluid dynamics (CFD) and reaction modelling study of bio-oil catalytic hydrodeoxygenation in microreactors - Hafeez, Sanaa; Aristodemou, Elsa; Manos, George; Al-Salem, S. M.; Konstantinou, Achilleas (My University, 2020)
A computational fluid dynamics (CFD) model was derived and validated in order to investigate the hydrodeoxygenation reaction of 4-propylguaiacol, which is a lignin-derived compound present in bio-oil. A 2-D packed bed microreactor was simulated using a pre-sulphided NiMo/Al2O3 solid catalyst in isothermal operation. A pseudo-homogeneous model was first created to validate the experimental results from the literature. Various operational parameters were investigated and validated with experimental data, such as temperature, pressure and liquid flow rate, and it was found that the CFD findings were in very good agreement with the results from the literature. The model was then upgraded to that of a detailed multiphase configuration, and phenomena such as internal and external mass transfer limitations were investigated, as well as reactant concentrations on the rate of 4-propylguaiacol. Both models were in agreement with the experimental data, and therefore confirm their ability for applications related to the prediction of the behaviour of bio-oil compound hydrodeoxygenation.
Keywords: Biomass; Pyrolysis; Simulations; Chemistry; Membrane; Acetone